Environmental Life Cycle Assessment of an Airborne Radar System - Abshir, Ahmed; Munck Larsson, Viktor (My University, 2025)
This thesis presents a comprehensive Life Cycle Assessment (LCA) of an airborne radar system developed by Saab Surveillance, conducted in accordance with ISO 14040 and 14044 standards. The study evaluates the environmental impacts of the radar across its entire life cycle, from raw material extraction to endof- life, focusing on key impact categories including Global Warming Potential (GWP), Acidification, Eutrophication, Mineral Resource Scarcity, and Terrestrial Ecotoxicity. The assessment identifies the use phase as the predominant contributor to environmental impact, accounting for over 90% of total emissions in most categories, primarily due to fuel combustion associated with airborne operation. However, as this phase lies largely outside the control of Saab Surveillance, a complementary scenario excluding the use and test phases was conducted to better identify actionable environmental hotspots within the company’s sphere of influence. Detailed analysis of the assembly phase revealed that components containing printed circuit boards, especially those with gold-plated finishes, exert a disproportionately high environmental burden per kilogram, driven by the energy-intensive and material-intensive processes associated with gold production. Furthermore, structural components made from iron-nickel-chromium alloys were found to contribute significantly to acidification and resource depletion due to nickel-related emissions. Recommendations for improving the environmental performance of the radar system include adopting more aerodynamic and lightweight designs, sourcing materials from low-emission suppliers, utilizing alternative plating methods such as nickel-palladium-gold, and exploring bio-based composite materials. Additionally, the study highlights the potential benefits of implementing a formal end-of-life disposal plan and considering take-back systems for high-impact components such as PCBs. The results provide a strategic foundation for Saab Surveillance to reduce its environmental footprint, enhance supply chain sustainability, and align future product development with ecological and regulatory expectations.
Keywords: Life Cycle Assessment; Environmental Hotpsots; Gold-plating